(untitled) (Research, Society and Development, 2020)
Objective: To analyze the risk factors for stroke in young men and women. Method: Cross-sectional, quantitative study, carried out with 1073 young adults. Data were collected using a form and, to associate risk factors with sex, the chi-square and odds ratio were used. To adjust the model, logistic regression was used. Results: Women reported more stroke in the family than men, higher level of physical inactivity and had higher cholesterol levels, as well as a higher proportion of them were on an unbalanced diet; in turn, men reported more smoking and alcohol use and more altered blood glucose and blood pressure levels. After adjustment, there was a significant association between sex and: smoking, cholesterol classification, blood pressure and excess weight. Conclusion: Men had more smoking and more pre-hypertension / hypertension and women had higher levels of cholesterol and excess weight.